CREATIVITY AND INNOVATION IN SMALL BUSINESS: A DIGITAL SYSTEM LITERATURE REVIEW WITH ROUND MAP NEW NORMAL - Hasrudy Tanjung; Yunus Handoko; Irwan Syari Tanjung; Sherlinda Octa Yuniarsa (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this research is to analyze a creativity and innovation in small business ability with a digital system literature review. Because of a fluctuation on local industry such as culinary, fashions, tourism, and management. This research can review by digital collaboration systems about design for content creator. This research was used by a research round map, such as depth interview informants and review. Then, take a sample with gathering all data using research instruments. Therefore, it was provide some estimated of future demand, given data on the underlying driven in Indonesia. So, any entrepreneurship in local industry did not survive to manage their business. In this case, it was need to discuss with all teams like internal for being either stuffed by development a new products with minimum cost. Moreover, local communities that have been tried to make innovation for their product, which not enough tough the market in short-term space off.Keywords: creativity, innovation, small business, review